Acute resistance exercise: Physiological and biomechanical alterations during a subsequent swim training session - Arsoniadis, G. G.; Bogdanis, G. C.; Terzis, G.; Toubekis, A. G. (International Journal of Sports Physiology and Performance, 2020)
Purpose: To examine the acute effect of dry-land strength training on physiological and biomechanical parameters in a subsequent swim training session. Methods: Twelve male swimmers (age: 19.0 [2.2] y, peak oxygen uptake: 65.5 [11.4] mL/kg·min) performed a 5×200-m test with progressively increasing intensity. Blood lactate (BL) concentration was measured after each 200-m bout, and the speed corresponding to 4 mmol/L (V4) was calculated. In the experimental (EXP) and control (CON) conditions, swimmers participated in a swim training session consisting of 1000-m warm-up, a bout of 10-second tethered swimming sprint, and 5×400 m at V4. In EXP condition, swimmers completed a dry-land strength training session (load: 85% of 1-repetition maximum) 15 minutes before the swimming session. In CON condition, swimmers performed the swimming session only. Oxygen uptake, BL concentration, arm-stroke rate, arm-stroke length, and arm-stroke efficiency were measured during the 5×400 m. Results: Force in the 10-second sprint was not different between conditions (P=.61), but fatigue index was higher in the EXP condition (P=.03). BL concentration was higher in EXP condition and showed large effect size at the fifth 400-m repetition compared with CON condition (6.4 [2.7] vs 4.6 [2.8] mmol/L, d=0.63). During the 5×400 m, arm-stroke efficiency remained unchanged, arm-stroke length was decreased from the third repetition onward (P=.01), and arm-stroke rate showed a medium increment in EXP condition (d=0.23). Conclusions: Strength training completed 15 minutes before a swim training session caused moderate changes in biomechanical parameters and increased BL concentration during swimming. Despite these changes, swimmers were able to maintain force and submaximal speed during the endurance training session.